Risk factors for renal disease and diabetes in remote Australia - findings from The Western Desert Kidney Health Project - Christine Jeffries-Stokes; Annette Stokes; Lachlan McDonald; Sharon Evans; Linda Anderson (deceased); Priscilla Robinson (James Cook University, 2020)
Introduction: The Western Desert Kidney Health Project (WDKHP) aimed to determine the prevalence of type 2 diabetes (T2DM), kidney disease and associated risk factors in Aboriginal and non-Aboriginal people in a remote area of Western Australia.Methods: The project, featuring whole-of-community cross-sectional surveys and health assessments using point-of-care testing, was conducted in five small towns and six remote Aboriginal communities in the Goldfields of Western Australia between 2010 and 2014. Initial health assessments were completed by 597 adults (424 Aboriginal) and 502 children (393 Aboriginal). This included almost 80% of the Aboriginal population. All non-Aboriginal people residing in the six remote Aboriginal communities participated.Results: Risk factors for renal disease and T2DM were present in participants of all ages, including children as young as 2 years. There was no significant difference between Aboriginal and non-Aboriginal children. Aboriginal and non-Aboriginal adult participants had twice the burden of T2DM than the standard Australian population. More than 12% of all children had elevated albumin-creatinine ratio (ACR). Adults had markers of kidney disease at higher rates than expected: 51% of Aboriginal adults and 27% of non-Aboriginal adults had at least one marker of kidney disease (haematuria, proteinuria or elevated ACR). Aboriginal women were the highest risk group (32% T2DM, 40% elevated ACR). Haematuria and low urine pH were common findings, 21% of people had haematuria (greater than trace) and 71% had urine pH of 6 or less; there was no difference in this finding between Aboriginal and non-Aboriginal people.Conclusion: The WDKHP found higher than expected rates of risk factors for T2DM and renal disease compared with Australian Bureau of Statistics rates for Australian Aboriginal and non-Aboriginal adults and children, with Aboriginal women the highest risk group. The rates for non-Aboriginal participants were higher than expected, suggesting exposures in common might be more important than ethnicity.The high prevalence of aciduria and haematuria found in both Aboriginal and non-Aboriginal participants in this study suggests that factors contributing to a chronic metabolic acidosis and inflammation or irritation of the urinary tract need to be explored. Drinking water quality in this remote area is known to be poor and may be an important contributing factor. Many of the contributing factors are potentially modifiable - such as water quality, food supply, exercise opportunities and living conditions - offering scope for interventions to reduce the risk and burden of these diseases.